Biologia de nidificação e estrutura sociogenética intranidal em espécies de Trypoxylon (Hymenoptera:Crabronidae) - Santoni, Mariana Marchi (Universidade Federal de São Carlos, 2008)
Female wasps of the genus Trypoxylon (Hymenoptera: Crabronidae) mass-provision their nests with paralyzed spiders. Some species build mud nests; others use preexisting tubular cavities that are divided into a linear series of cells separated by mud partitions. Males of the Trypargilum subgenus mate with the females at the time a nest is initiated and guard the nest until it is completed, helping the female in the building and provisioning activities. In this study, the biology of the nest building and nest genetic structure of four species of Trypoxylon (Trypargilum) T. rogenhoferi, T. lactitarse, T. aurifrons and T. nitidum are shown. The species were sampled using trap-nests (made of dry bamboo stems) in three localities of the state of São Paulo: Araras (three years), São Carlos and Rifaina (two years). These areas were divided in sampling sites. The trap-nests used by the wasps were replaced with new ones and transported to the laboratory and they had the cocoons individually placed in vials. The emerged adults were identified and their emergency, weight and sex were registered. Later, they were stored at -20ºC. Alloyme phenotypes determined through horizontal starch gel electrophoresis were used to the determination of the intranidal relatedness. Some adults were submitted to morphometric analysis of wing traits (length and width of the forewing and hindwing) and mitocondrial DNA analysis. It was collected 2,908 nests of solitary hymenopterans, and 2,478 were founded by Trypoxylon females. Nesting activity was higher in the warm-rainy season (October-March) in these species. The trap-nests used by the different species showed significantly different dimensions. Araneidae was the spider family mainly used for provision, but a species-specific provisioning was observed. The most important parasitoid of the four species was Melittobia. In the three areas, the different species of Trypoxylon coexist temporally but each of them built their nests frequently in a specific site. This result may suggest differential occupation of the habitat. The intranidal architecture of the studied species does not differ from other species of the Trypargilum subgenus: the females divide the nest-trap in sequences of provisioned cells and finish it with the construction of a closure plug. Two types of T. rogenhoferi and T. lactitarse cocoons were found, as observed for other species of the group punctulatum. It was verified that the frequencies of the two types are associated with sex and nest-trap diameter. A possible genetic determination of this character is discussed. A 1 :1 populational sex ratio for the four species was found during all the periods for Araras and Rifaina and the distribution of the sexes inside the nest was not random, where males were frequently found in the first brood cells. Females were significantly bigger than males for the five traits, showing a higher parental investment in females. The developmental cycle in these species last 30 days and a short diapause was observed in T. rogenhoferi and T. lactitarse in the cold-dry season. The allozyme analyses indicated that most of the nests show phenotypes according to a monoginy/monandry hypothesis. Although this result clearly suggest that the male-guard behavior confers him the paternity of the female offspring, some extra-pair matings were also observed.
Keywords: Crabronidae; Sazonalidade; Habitat (Ecologia); Alocação sexual; Parentesco; Alozimas; CIENCIAS BIOLOGICAS::GENETICA